Downregulation of inflammatory mediators by ethanolic extract of Bergenia ligulata (Wall.) in oxalate injured renal epithelial cells. (15th July 2021) - Singh, Anubha; Tandon, Simran; Nandi, Shoma Paul; Kaur, Tanzeer; Tandon, Chanderdeep
Abstract: Ethnopharmacological relevance: In the Indian traditional system of medicine, Bergenia ligulata (Wall.) Engl. has been used for treatment of urolithiasis. Its efficacious nature has led to its incorporation in various commercial herbal formulations such as Cystone and Neeri which are prescribed for kidney related ailments. Aim of the study: To assess whether ethanolic extract of B. ligulata can mitigate the cascade of inflammatory responses that cause oxidative stress and ultimately cell death in renal epithelial cells exposed to hyperoxaluric conditions. Material and methods: Bioactivity guided fractionation using solvents of varying polarities was employed to evaluate the potential of the extracts of B. ligulata to inhibit the crystallization process. Modulation of crystal morphology was visualized through Scanning electron microscopy (SEM) analysis. Cell death was assessed using flow cytometry based assays. Alteration in the inflammatory mediators was evaluated using real time PCR and immunocytochemistry. Phytochemical characterization of the ethanolic extract was carried out using FTIR, LC-MS and GC-MS. Results: Bioactivity guided fractionation for the assessment of antilithiatic activity revealed dose dependent inhibition of nucleation and aggregation process of calcium oxalate crystals in the presence of various extracts, however ethanolic extract showed maximum inhibition and was chosen for further experiments. Studies on renal epithelial NRK-52E cells showed, cytoprotective efficacy of B. ligulata extract against oxalate injury. SEM anaysis further revealed the potential of the extract to modulate the crystal structure and adhesion to renal cell surface. Exposure of the renal cells to the extract led to conversion of the calcium oxalate monohydrate (COM) crystals to the less injurious calcium oxalate dihydrate (COD) form. Expression analysis for oxidative stress and inflammatory biomarkers in NRK-52E cells revealed up-regulation of Mitogen activated protein kinase (MAPK), Osteopontin (OPN) and Nuclear factor- ĸB (NF-ĸB), in response to calcium oxalate insult; which was drastically reduced in the presence of B. ligulata extract. Flow cytometric evaluation pointed to caspase 3 mediated apoptotic cell death in oxalate injured cells, which was attenuated by B. ligulata extract. Conclusion: Considering the complex multifactorial etiology of urolithiasis, ethanolic extract from B. ligulata can be a promising option for the management of kidney stones, as it has the potential to limit inflammation and the subsequent cell death. Graphical abstract: Image 1